2018
DOI: 10.3389/fpsyg.2018.02059
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Tactile Temporal Discrimination in Patients With Hepatic Encephalopathy

Abstract: The sensory system constantly receives stimuli from the external world. To discriminate two stimuli correctly as two temporally distinct events, the temporal distance or stimulus onset asynchrony (SOA) between the two stimuli has to exceed a specific threshold. If the SOA between two stimuli is shorter than this specific threshold, the two stimuli will be perceptually fused and perceived as one single stimulus. Patients with hepatic encephalopathy (HE) are known to show manifold perceptual impairments, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A recent study identified HE as an impairment of the brain function caused by liver failure and portosystemic blood shunting, characterized by emotional impairment, cognitive dysfunction, psychiatric problems, and neuromuscular dysfunction [4,5]. Moreover, the patients with HE present impaired visual temporal perception [6] and impaired tactile temporal discrimination [7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified HE as an impairment of the brain function caused by liver failure and portosystemic blood shunting, characterized by emotional impairment, cognitive dysfunction, psychiatric problems, and neuromuscular dysfunction [4,5]. Moreover, the patients with HE present impaired visual temporal perception [6] and impaired tactile temporal discrimination [7].…”
Section: Introductionmentioning
confidence: 99%